Avaliação de diferentes protocolos de IATF em vacas de raça tabapuã de diferentes categorias - Galon, Naidiel Renã (2020)
Brazilian livestock breeding, even developing exponentially, it is still considered a low productivity activity due to the lack of efficiency in production. To improve this scenario, the production pillars must be exploited with maximum efficiency, trying to keep the animals healthy, well managed, nourished and good reproductive health, thus, it is possible to generate a higher number of good quality calves in the productive life of a parent on a farm, where it is known that the challenge is superior compared to the other categories. In order to define the best protocol of Artificial Insemination by Fixed Time in multiparous cows of Tabapuã breed in southwestern Paraná, were tested in two groups, with different dates, four protocols of three managements, used to differentiate from the standard protocol the GnRH and/or eCG, also evaluating with the aid of ovarian activity at the beginning of the treatments, where these drugs, when used isolated way or in combination, reacted positively, even in animals with adequate body condition index. The ages of each cow also proved to be an important point to consider, where primiparous and cows older than 7 years presented the worst results due to slower puerperal recovery. The conception rate was measured from the confirmation of pregnancy using ultrasound.